Exportin-inspired artificial cell nuclear-exporting nanosystems. Issue 12 (18th May 2022) - Inui, Mitsuo; Hamada, Yuta; Sejima, Nana; Ueda, Natsumi; Katayama, Tokitaka; Ono, Kimika; Nagahama, Koji
Abstract : Inspired by the structural and chemical features of importin/exportin, we developed an artificial nuclear-exporting nanosystem capable of eliminating compounds accumulated abnormally in the nucleus. Abstract : Inspired by the structural and chemical features of naturally occurring importin/exportin that allows them to pass through the nuclear pore complexes, we successfully developed an artificial nuclear-exporting nanosystem capable of eliminating compounds accumulated abnormally in the nucleus.